Intra-Articular Laser Therapy May Be a Feasible Option in Treating Knee Osteoarthritis in Elderly Patients. (22nd November 2022) - Chen, Jean-Lon; Hsu, Chih-Chin; Chen, Wesley C. C.; Peng, Yu-Ning; Chen, Carl P. C.; Suputtitada, Areerat
Abstract : Knee osteoarthritis (OA) is a common problem in elderly patients. They are often troubled with altered knee function, such as pain and weakness. However, not all these patients are able to receive autologous platelet-rich plasma (PRP) injections as they may be taking antiplatelet or anticoagulant medications. Their physical condition may not allow them to receive total knee replacement surgery as well. Long-term oral intake of nonsteroidal anti-inflammatory drugs may be detrimental to the gastrointestinal tract. As a result, it is crucial to discover new treatment options that can alleviate painful knee symptoms in elderly knee OA patients. In this study, 19 elderly patients diagnosed with moderate degree of knee OA as well as suprapatellar bursitis were recruited. They received low-level laser therapy (LLLT) to their affected knees. Under ultrasound guidance, flexible fiber optic wire was inserted intra-articularly into the knee joint. Red laser followed by infrared irradiation was performed once every 2 weeks for a total of 3 times. The Lequesne index for knee OA and the volume of suprapatellar synovial fluid (SF) were measured. SF proteomic analyses were also performed up to a period of 6 months. The results revealed that after 3 LLLT, the Lequesne index significantly decreased, signifying improvement in the knee joint functional status. The volume of suprapatellar SF and SF proteins associated with inflammation also decreased significantly in the SF. These findings lasted up to a period of at least 3 months. Therefore, LLLT may be considered as a feasible option in treating elderly patients with knee OA who are not suitable for surgical interventions or intra-articular PRP injections.